An international review of the challenges associated with securing 'buy-in' for water safety plans within providers of drinking water supplies - Summerill, Corinna; Smith, Jennifer A.; Webster, James; Pollard, Simon J. T. (IWA Publishing, 2010)
Since publication of the 3rd Edition of the World Health Organisation (WHO) Drinking Water Quality guidelines, global uptake of water safety plans (WSPs) has been gathering momentum. Most guidance lists managerial commitment and ‘buy-in' as critical to the success of WSP implementation; yet the detail on how to generate it is lacking. This review discusses aspects of managerial commitment to WSPs. We argue that the public health motivator should be clearer and a paramount objective, not lost among other, albeit legitimate, drivers such as political or regulatory pressures and financial efficiency.